THE EFFECT OF DIETARY SUPPLEMENTATION OF Sargussum wightii EXTRACT ON Clarias gariepinus PHYSIOLOGICAL RESPONSES - Aderolu, Ademola Zaid; Ishola, Ismail O.; Aluta, Uzeme Precious; Williams, Boluwatife O. (Indonesian Aquaculture Journal, 2024)
Seaweeds are becoming vital feed materials due to their high concentration of nutrients and active secondary metabolites. In this context, the brown seaweed Sargassum wightii extract (SWE) was included in Clarias gariepinus diets to investigate its effects on growth rate, nutrient utilization, haemato-biochemical indices, antioxidant activities and immune responses. Four experimental diets with four different levels (control- 0 %, 0.25 %, 0.5 %, and 1.0 %) of SWE were fed to four triplicate groups of C. gariepinus juvenile (mean initial weight 14.50 ± 0.00 g) for 28 days. At the end of the feeding trial, there was no significant difference (p>0.05) in the growth performance of fish groups fed SWE and the control group. However, there were significant differences (p<0.05) in feed conversion ratio and protein efficiency ratio between the control and SWE groups. Erythrocytes, leukocytes, haemoglobin, lymphocytes, and high-density lipoprotein cholesterol in fish fed SWE supplemented diets were significantly higher (p<0.05) than control. Notably, the liver function enzyme- Alkaline phosphatase was significantly higher (p<0.05) in fish fed SWE diets when compared to the control group. There was significant variation (p<0.05) in hepatic antioxidant enzymes activities across all diets. It was also observed that TNF-α, IL-6 and IL-β increased significantly in the liver of C. gariepinus fed SWE supplemented diets compared to control. Therefore, these results suggest that inclusion of S. wightii extract in the fish diet, although did not enhance growth performance, could improve the immune status and reduced oxidative stress of C. gariepinus.